MERGER & AKUSISI DAN KINERJA PERUSAHAAN - Setiawan, Rahmat; Adriani, Mirza (2021)
The purpose of this paper is to analyse the effect of merger & acquisition (M&A) on firm performance. This type of research is quantitative and multiple linear regression as the method. This research used 88 observations of non-financial companies who did M&A and listed on the IDX (Indonesia Stock Exchange) during 2010 until 2015. Firm fermormance as measured by ROA (return on asset) as the dependent variable in this study. M&A as independent variable in this study. This research results indicated that M&A has a significant negative effect on company performance.